2021
DOI: 10.3390/ijms22126183
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Glutathione Redox Status as a Possible Tumor Marker in Colorectal Cancer

Abstract: The role of oxidative stress (OS) in cancer is a matter of great interest due to the implication of reactive oxygen species (ROS) and their oxidation products in the initiation of tumorigenesis, its progression, and metastatic dissemination. Great efforts have been made to identify the mechanisms of ROS-induced carcinogenesis; however, the validation of OS byproducts as potential tumor markers (TMs) remains to be established. This interventional study included a total of 80 colorectal cancer (CRC) patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…A comprehensive study of 150 patients with CRC who underwent surgery analyzed OS parameters (MDA and 4-HNE) in peripheral and mesenteric blood according to four tumor stages (I-IV). The authors observed that levels of both OS markers increased with tumor stage [ 58 ], in line with previous results published by our group [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A comprehensive study of 150 patients with CRC who underwent surgery analyzed OS parameters (MDA and 4-HNE) in peripheral and mesenteric blood according to four tumor stages (I-IV). The authors observed that levels of both OS markers increased with tumor stage [ 58 ], in line with previous results published by our group [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Dusak et al also reported decreased levels of GSH in the serum of 25 CRC patients with respect to healthy controls [ 16 ]. Serum levels of GSH and GSSG and the GSSG/GSH ratio have been pointed to as potentially effective TMs, not only in CRC, but in other types of cancer [ 28 ]. Rasool et al, in a study of 50 CRC patients and 20 controls, detected lower levels of CAT and GSH in the serum of patients with respect to controls, which, once again, is in accordance with our results [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the ratio of GSH/GSSG is about 100:1 under physiological condition [ 34 ]. Decreased level of GSH in cancer cells results is often associated with defective response to oxidative stress [ 35 ]. Since S-glutathionylation is a reversible modification on cysteine residues of proteins, evaluating the levels of blood GSH and GSH/GSSG could well reflect the status of glutathionylated Hsp90 in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione redox status in terms of GSH/GSSG is an important tumour biomarker of CRC [55] and can be used in non-invasive CRC diagnosis. GSH/GSSG of the CRC model reduced after integrating the RS module to the CRC model due to the increase in the flux activity of GSSG producing reactions.…”
Section: Discussionmentioning
confidence: 99%